New Travelling Wave Solutions of Two Nonlinear Physical Models by Using a Modified Tanh-Coth Method. Issue 1 (March 2015) - Gözükizil, Ömer Faruk; Salhi, Abdellah
In this work, a modified tanh – coth method is used to derive travelling wave solutions for (2 + 1)-dimensional Zakharov-Kuznetsov (ZK) equation and (3 + 1)-dimensional Burgers equation. A new variable is used to solve these equations and established new travelling wave solutions.